Research on General Secretary Xi Jinping’s Important Discourse on Excellent Traditional Chinese Culture - Liu, Yajing (International Journal of Social Sciences and Public Administration, 2025)
Since China entered a new era, General Secretary Xi has attached great importance to the value of the Chinese culture and made a series of important discussions on the traditional Chinese culture. These discussions are profound and logical, indicating the direction for the development of the excellent traditional Chinese culture. The paper takes these important discussions and research contents, starting from theory and practice, using literature investigation method, systematic analysis method and history and logic and other research methods, overall analysis and systematic summary, in order to form a more systematic and complete cognition. It will help us to grasp traditional culture and become powerful inheritors and inheritors of it.